Cereal Bank as a Necessary Rural Livelihood Institute in Arid Land, Makoja Village, Dodoma-Tanzania - Msaki, Mark M; Mwenda, Michael I; Regnard, Irene J (Asian Economic and Financial Review, 2013)
In 2012, the study was carried at Makoja Village, in Semi-Arid region of Dodoma. The aim of the conducted study was to assess the importance of Cereal Bank to livelihood of farming households. A total of 80 respondents were interviewed. Data were analyzed using SPSS 16.0 computer program. The major findings of the study revealed that, almost all of the households (96.2 %) were poor, while more than a half of the sampled population was chronically food insecure. Income and expenditure analysis revealed that households had no opportunity to manage savings. Further analysis on expenditure revealed that despite being farming households, the later spent large proportion of their income in purchasing food for households. Cereal bank has been potential to provide food at the time of less, storage facility, seed stocking facility and a business opportunity. Cereal banks should be purposively promoted to improve livelihood and assure food security in the rural areas.